Tiwanaku ceramic style and its influence on theory, interpretation, and conclusions of Andean archaeologists - Haupt, Beth M. (Archaeological Studies Program, University of Wisconsin-La Crosse, 2007)
This paper investigates the interpretation of ceramic style in the context of Andean Archaeology. I will focus specifically on the ceramics of the Tiwanaku people that occupied the Lake Titicaca Basin for nearly a thousand years. Andean scholars have used two general approaches to the interpretation of Tiwanaku material culture, one emphasizing a bottom-up or local perspective and the other emphasizing a top-down capital-centric perspective. This project evaluates how scholars have used remains of ceramics to analyze the emergence and spread of Tiwanaku influence within the context of these two theoretical frameworks, and how each perspective has contributed to a better understanding of Tiwanaku civilization.
Keywords: Indian pottery -- Bolivia -- Tiwanaku Site; Indian pottery -- Bolivia -- Lukurmata Site; Tiwanaku culture; Archaeology -- Methodology